GWAS analysis reveals a novel ERF family gene GH_A03G1754 in upland cotton under cold stress - Jianbin Li; Xiaokang Feng; Bangxin Chen; Qian-Hao Zhu; Xinyu Zhang; Yonglin Yang; Fei Xue; Jie Sun (Plant Stress)
Low temperature is a critical abiotic stress during the early growth stages of cotton, affecting crop establishment and causing yield reduction. A thorough insight into the genetic factors governing cold tolerance is critical for formulating breeding strategies aiming for enhanced cold-tolerance. This study measured the primary root length (RL), fresh weight (FW), and dry weight (DW) of 343 upland cotton (Gossypium hirsutum L.) germplasm under sustained low-temperature stress during the seedling stage. The single nucleotide polymorphisms (SNPs) identified based on resequencing of the 343 accessions were used in a genome-wide association analysis of the three traits, which identified two, six and eight SNPs significantly associated with RL, FW, and DW, respectively. Two major loci on chromosomes A03 and D04 contributing to FW- and DW-based cold tolerance were evident due to their occurrence in at least two datasets. Within these two loci, multiple genes were found to be cold responsive, with GH_A03G1754 being a potentially positive contributor of cold tolerance, because silencing the gene in cold-tolerant variety reduced its cold tolerance. This study provides molecular markers and candidate gene for molecular breeding of cold tolerance in cotton.